DIGITAL MARKETING BRILLIANT ENGLISH COURSE (KAMPUNG INGGRIS PARE, KEDIRI) DI ERA PANDEMI COVID-19 - Nadya Sawitri; Tira Fitriawardhani; Muhammad Fadeli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2022)
At the end of 2019 a new type of virus called covid-19 emerged which spread throughout the country including Indonesia. Lots of people have been affected by the covid-19 pandemic, one of the companies that has been affected is the Brilliant English Course, many activities have had to be changed due to the covid-19 pandemic, one of which is digital marketing activities. The purpose of this study is to find out how digital marketing activities are carried out by the Brilliant English Course (KampungEnglish Pare, Kediri) in the era of the Covid-19 pandemic by utilizing social media. This study uses a qualitative descriptive research method in which the data is collected by interviewing informants and observing. The subject of this research is the Brand Ambassador Brilliant English Course and the object of this research is the Digital Marketing Brilliant English Course. The results of this study are that Digital Marketing implemented by Brilliant English Course aims to promote which in carrying out digital marketing Brilliant English Course is based on indicators, namely cost/transaction, incentive program, site design, interactive, Brilliant English Course has also succeeded in increasing the number of members.